Female infants are more susceptible to the effects of maternal antenatal depression; Findings from the Pelotas (Brazil) Birth Cohort Study - Netsi, E; Coll, CVN; Stein, A; Silveira, MF; Bertoldi, AD; Bassani, DG; Wehrmeister, FC; Domingues, MR (Elsevier, 2020)
Background: We utilised data from the 2015 Pelotas Birth Cohort, a large prospective cohort in southern Brazil, to examine the association of moderate and severe antenatal depression with child birth outcomes and explore interactions with sociodemographic characteristics.